The Prognostic Value of High Pretreatment Plasma D-Dimer Levels in Non-Metastatic Breast Cancer Patients with Absence of Venous Thromboembolism - (:unkn) unknown (AKAD DOKTORLAR YAYINEVI, 2016)
Systemic activation of coagulation and fibrinolysis is frequently observed in cancer patients without thrombosis. Recent studies have showed the association between D-Dimer (DD) and metastatic spread and prognosis of cancer. We aimed to investigate the prognostic value of DD in patients with non metestatic breast cancer (nMBC) and evaluated the DD levels and other variables for overall survival (OS) using univariate and multivariate analyses in 448 patients. The median follow-up time was 50 months (3-151 months). There was only significant relationship between DD and distant metastases (p=0.052). Performance status (PS) (p<0.001 and < 0.001), stage (p<0.001 and < 0.001), CEA (p<0.001 and < 0.001), CA 15-3 (p<0.001 and < 0.001) and DD (p<0.001 and 0.034) were determined as prognostic factors for OS in univariate analysis. In multivariate analysis, PS (ECOG 0 vs ECOG 1, p=0.022; ECOG 0 vs ECOG >= 2, (p<0.001), stage (stage I vs stage II, p=0.566; stage I vs stage III, p=0.033), the CA 15-3 (p=0.048) and DD levels (p=0.015) were determined as independent prognostic factors for OS. In conclusion, pretreatment high DD level is an important prognostic factor in patients with non metastatic breast cancer and high DD levels were associated with poor outcome.
Keywords: D-Dimer; Non-metastatic breast cancer; Prognosis; CELL LUNG-CANCER; COLORECTAL-CANCER; BLOOD-COAGULATION; SURVIVAL; MARKER; ACTIVATION; MORTALITY; STAGE; METASTASIS; RECURRENCE